Type 1 diabetes in DKA with hypogonadotropic hypogonadism and pituitary apoplexy – A diagnostic dilemma (Indian Journal of Case Reports, 2024)
A 17-year-old underweight boy came with a classical emergency of diabetic ketoacidosis associated with two additional clinical features; persistently low blood pressure despite adequate fluid resuscitation and hypogonadal features with Tanner stage 3 pubic hair, absent facial, and axillary hair along with a high-pitched voice. These findings triggered an endocrine workup which revealed hypogonadotropic hypogonadism. Suspecting primary pituitary pathology, an magnetic resonance imaging brain, was done which showed a well-defined hyperintense lesion in the pituitary suggestive of pituitary apoplexy. In the absence of headache, diplopia, and visual field defects, this incidental finding posed a dilemma regarding the diagnosis and management of diabetic ketoacidosis in the presence of apoplexy.